Aplikasi Cetakan Permanen untuk Meningkatkan Produksi dan Kualitas Produk IKM Pengecoran Logam Kuningan di Ngawen, Sidokarto, Godean, Yogyakarta - Suyitno Suyitno; Urip Agus Salim; Muslim Mahardika (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2016)
Small and Medium Enterprises (SME) brass foundry in Ngawen Sidokarto, District of Godean, Sleman, Yogyakarta mostly produced cow necklace accessories (klonthong) and jathilan accessories (klinthing). Te industry and business management are arranged within the scope of family. Te products are relatively low in quality and its market share is limited and tend to be traditional. Tis condition is caused by the weak knowledge of the management and the method of casting metals and metal science. Brass casting methode, that was used at IKM partner, is casting with mold of sand or soil. Tis process requires the making process of sand molds, that is removed afer the brass solidify. For large quantities products, this process is inefcient and takes a long time. It would require a more efcient and faster method in the production process. Method of sand casting and ceramics have been used by SMEs cast brass in Yogyakarta, however it  has many disadvantages in terms of increased productivity and quality as well as the expansion of product applications. Te permanent mold casting of iron is a casting method which has many advantages over other methods, but the use for SMEs has not been applied in the SME of cast brass. Te permanen mold casting methods was introduced to SME partners. Tis replaces the sand mold materials and molding sand. It is expected the casting process is faster because the mold can be used for a large number of products. Te results show that the application of the technology results in products with precision and consistent in shape and size. Community Service of UGM with Appropriate Technology has also collaborated with  Industry and Trade service of Yogyakarta donation of production machinery for making permanent mold. It can be concluded that the application of permanen mold in the brass foundry industry improve the product precision and the speed of produsction.